Limosilactobacillus reuteri Y15 enhances uterine development and function in gilts via the gut-uterus axis - Juanli Huo; Shen Li; Dongxin Lu; Lei Li; Weidong Zhang; Yukang Li; Bin Yao; Yong Zhao; Yawei Zhang; Jie Zhang; Huiying Luo (Theriogenology, 2026)

Low-intensity electrical stimulation enhances phthalate ester biodegradation by activated sludge through real-time multi-scale regulation - Huabo Gong; Zhuo-Ning Xian; Jinwen Hu; Jinming Luo; Yawei Wang; Xiaowei Liu; Nanwen Zhu (Water Research, 2026)

Experimental investigation of oxygen-enriched combustion in conjunction with plasma ignition and plasma-assisted combustion to improve ammonia combustion - Chen Wu; Qifu Lin; Dianwu Wu; Chengzhou Liu; Shilong Zhong; Hansheng Feng; Longwei Chen; Zhenyang Li; Yiman Jiang; Guangnan Luo; Yawei Song; Weiye Chen; et al. (Fuel, 2026)

The Priming Impacts of Early Hypoxia Exposure in Abalone Parents Are Transmitted to Offspring - Yawei Shen; Yue Dai; Qizhen Xiao; Miaoqin Huang; Xuan Luo; Caihuan Ke; Weiwei You (Molecular Ecology, 2026)
The early environmental disturbances may have lasting effects on the sensitivity and acclimation abilities of organisms in later life stages or even in subsequent generations. However, measuring the responses of marine species with long generation times across multiple generations is challenging. Here, we investigated the inter‐generational carryover effects of early hypoxia exposure on Pacific abalone ( Haliotis discus hannai ), which takes two years to reach reproductive maturity. A five‐year study revealed that embryonic hypoxia exposure in abalone parents (F 0 ) has long‐lasting effects, which makes offspring (F 1 ) have higher specific growth rates and hypoxia tolerance despite these offspring having never been exposed to hypoxia. Embryonic hypoxia exposure did not reduce the genetic diversity ( Na , Ne , I , Ho , He and F ) of abalone between two generations, nor did it result in genetic differentiation ( F st and Nei's genetic distance) within a single generation. However, natural selection during the two‐year culture period may have favoured F 0 individuals with superior fitness traits to survive, ultimately driving genetic divergence among the F 1 generation. Furthermore, differentially expressed genes (e.g., mthfr and shmt1 ) that reflect the single‐generational, inter‐generational, and multi‐generational effects were involved in methylenetetrahydrofolate reductase activity and one carbon pool by folate. These genes might mediate the process by which F 0 embryonic hypoxia exposure alters the adaptive traits of the F 1 generation. This study revealed that the priming impacts of early hypoxia exposure might persist across generations through both genetic and non‐genetic mechanisms, providing insights for protecting marine organisms under global climate change.

Understanding the differences in ignition and combustion characteristics between raw coal and pyrolyzed char: A combined PLIF measurement and DFT calculation - Yawei Song; Sheng Su; Qifu Lin; Longwei Chen; Chengzhou Liu; Weiye Chen; Zhenyang Li; Yiman Jiang; Dianwu Wu; Hansheng Feng; Guangnan Luo; Jun Xiang (Fuel, 2026)

A methodical comparative analysis of the improved dechlorination of trichloroethylene (TCE) using C-, N-, and S-modified zero-valent iron (ZVI) - Xiang Luo; Hongwei Chen; Hongjian Shen; Ling Zhang; Jinbo Chen; Shuai Liu; Bo Gao; Honglei Zhang; Yawei Gu (Journal of Water Process Engineering, 2026)

Physical Activity and Depressive Mood Share the Structural Connectivity Between Motor and Reward Networks - Shiqi Di; Na Luo; Weiyang Shi; Zhengyi Yang; Jing Sui; Rongtao Jiang; Yue Cui; Zongchang Du; Jiaqi Zhang; Yawei Ma; Haiyan Wang; Congying Chu; et al. (Neuroscience Bulletin, 2026)

ATP-citrate lyase is a critical regulator of physiological and pathological angiogenesis - Chong Xu; Ying Lin; Zeyu Wang; Cailin Feng; Lingfeng Luo; Shuai Guo; Han Zhang; Lu Liu; Azhen Fan; Penglong Qi; Dongyang Jiang; Yiming Xu; et al. (Angiogenesis, 2026)

Occurrences and migration characteristics of photoinitiators in paper food packaging: Implication for human exposure - Chenge Qian; Lu Bai; Wen Wang; Yadan Luo; Juan Li; Yawei Wang (Journal of Environmental Sciences, 2025)

Seasonal variation in two culture systems and genome-wide association analysis of taurine content in the foot muscles of the Pacific abalone (Haliotis discus hannai) - Ziheng Yin; Junyu Liu; Wenchao Yu; Yawei Shen; Yang Gan; Yexin Chen; Jinwei Ke; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

Proteomic insights from extracellular vesicles into the molecular mechanisms of health effects induced by Per- and polyfluoroalkyl substances - Yanping Li; Yadan Luo; Yang Liu; Na Li; Kai Huang; Lingxiangyu Li; Zhigang Li; Chao Han; Nali Zhu; Yawei Wang; Guibin Jiang (Journal of Environmental Sciences, 2025)

Transcriptome analysis of hybrid abalone (Haliotis discus hannai ♀ × H. fulgens ♂) reveals non-additive effects contributing to growth heterosis at early summer water temperature in Fujian - Zekun Huang; Yawei Shen; Xingze Wang; Qizhen Xiao; Yi Wang; Yang Gan; Zhaofang Han; Wanbo Li; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2025)

The weak association between hypoxia tolerance and thermal tolerance increases the susceptibility of abalone to climate change - Yawei Shen; Yue Dai; Feng Yu; Wenzhu Peng; Junyu Liu; Weiwei You; Xuan Luo; Caihuan Ke; Nan Chen (Environmental Research, 2025)

Carryover effects of embryonic hypoxia exposure on adult fitness of the Pacific abalone - Yue Dai; Yawei Shen; Caihuan Ke; Xuan Luo; Miaoqin Huang; Huoqing Huang; Weiwei You (Environmental Research, 2024)

Prevalence of antibiotic resistance genes, heavy metal, and bacterial community composition in sea sediments influenced by Eriocheir sinensis breeding aquaculture - Hui Fu; Wei Sun; Yawei Cao; Qing Li; Xiaotong Wang; Zijie Zhou; Qian Meng; Tingyi Luo; Wei Gu; Qingguo Meng (Environmental Science and Pollution Research, 2024)

A high throughput method to assess the hypoxia tolerance of abalone based on adhesion duration - Yue Dai; Yawei Shen; Yanbo Liu; Weiwei Xia; Jiawei Hong; Yang Gan; Jie Huang; Xuan Luo; Caihuan Ke; Weiwei You (Aquaculture, 2024)

Macaque Brainnetome Atlas: A multifaceted brain map with parcellation, connection, and histology - Yuheng Lu; Yue Cui; Long Cao; Zhenwei Dong; Luqi Cheng; Wen Wu; Changshuo Wang; Xinyi Liu; Youtong Liu; Baogui Zhang; Deying Li; Bokai Zhao; et al. (Science Bulletin, 2024)

SPAN secondary particles enabled high energy density Lithium-Sulfur battery - Weijing Zuo; Rui Li; Xiangkun Wu; Yawei Guo; Shoubin Zhou; Bohua Wen; Jiayan Luo; Lan Zhang (Chemical Engineering Journal, 2024)

Optimization of leaf area index measurement method and correction of green plot ratio formula based on regional plant characteristics—a study in Chongqing, China - Lili Dong; Yawei Jiang; Yu Luo; Xiang Cheng; Lijiao Ai (Environmental Science and Pollution Research, 2024)

Low vaporization enthalpy hydrogels for highly efficient solar-driven interfacial evaporation - Qi Zhao; Yawei Yang; Benxin Zhu; Zuyi Sha; Hui Zhu; Zhixin Wu; Fahad Nawaz; Yumeng Wei; Lingdi Luo; Wenxiu Que (Desalination, 2023)

An overview of the mechanisms underlying hypoxia tolerance differences in aquatic animals and their inspirations for aquaculture - Yawei Shen; Weiwei You; Xuan Luo; Ying Lu; Miaoqin Huang; Caihuan Ke (Reviews in Fish Biology and Fisheries, 2023)

Development of near-infrared reflectance spectroscopy (NIRS) model and genome-wide association study for glycogen and protein content in Pacific abalone - Junyu Liu; Muzhi Zhou; Ziheng Yin; Dan Huang; Liyan Zhu; Weiguang Zou; Wenchao Yu; Yawei Shen; Zekun Huang; Weiwei You; Caihuan Ke; Xuan Luo (Aquaculture, 2023)

Identification of natural and anthropogenic sources and the effects of climatic fluctuations and land use changes on dust emissions variations in the Qinghai-Tibetan Plateau - Heqiang Du; Yawei Fan; Lihui Luo; Jie Liao; Zongxing Li; Xiufan Liu; Xinlei Liu; Xian Xue; Tao Wang (Agricultural and Forest Meteorology, 2023)

Nanocatalyst-triggered cascade immunoassay: Multi-model immunochromatography assay for sensitive detection of Salmonella typhimurium - Xuechi Yin; Jingxin Hou; Jing Guo; Jiawei Li; Di Yang; Linpin Luo; Leina Dou; Yawei Liang; Yanru Wang; Jianlong Wang; Daohong Zhang (Chemical Engineering Journal, 2023)

Metabolic and transcriptional responses demonstrating enhanced thermal tolerance in domesticated abalone - Feng Yu; Yawei Shen; Wenzhu Peng; Nan Chen; Yang Gan; Qizhen Xiao; Junyu Liu; Yisha Lu; Weihong Lin; Zhaofang Han; Xuan Luo; Weiwei You; et al. (Science of The Total Environment, 2023)

Genotype by environment interactions in feed efficiency of Pacific abalone (Haliotis discus hannai) reared at different water temperatures - Wenchao Yu; Yawei Shen; Junyu Liu; Weiguang Zou; Zekun Huang; Miaoqin Huang; Ying Lu; Jinwei Ke; Xuan Luo; Weiwei You; Caihuan Ke (Aquaculture, 2023)

Genome-wide association and transcriptome studies reveal the segregation mechanism of mantle markings in three-way cross hybrid abalone - Qizhen Xiao; Shihai Gong; Yawei Shen; Yisha Lu; Xinlian Lai; Wenzhu Peng; Zekun Huang; Zhaofang Han; Hongjing Ji; Yang Gan; Xuan Luo; Weiwei You; et al. (Frontiers in Marine Science, 2022)
Trait separation which often appears in shellfish progeny, has been commercially used in shellfish breeding projects. A three-way cross hybrid abalone was produced with heterosis in growth performance and thermal tolerance, and with segregation in mantle marking. However, the inheritance mechanism of mantle marking is unclear. In this study, mantle marking was demonstrated to be a qualitative trait, following simple Mendelian inheritance, through inheritance pattern analysis of the presence of black markings on the mantle in five families of three-way cross of hybrid abalone. Thermal tolerance of abalone was assessed by the Arrhenius breakpoint temperature (ABT) of cardiac performance and a correlation between mantle marking and thermal tolerance of abalone was verified. A genome-wide association study (GWAS) for mantle marking was conducted using 603,067 high-quality single nucleotide polymorphisms (SNPs) derived from 57 individuals with mantle markings (Y group) and 58 individuals without mantle markings (N group). A total of 493 SNPs that were significantly ( p < 2.32E–07) associated with mantle markings were mainly distributed on chromosome 15. In the potential significantly associated region, 80 genes, including pigmentation-related genes PTPRT , PTPRC , PNCA , and CALM4 were annotated. Transcriptome analysis of the two groups showed that the expression levels of these genes ( PTPRT , DDT-b , ATOX1 , SLC6A3 , and GSTO1 ) were significantly different, and they may play important roles in the formation of mantle markings in the three-way cross hybrid abalone. Overall, our data provide valuable information for deciphering the phenotype differences of mantle marking in three-way cross hybrid abalone and help in the molecular marker-assisted breeding in abalone.

Fluctuations in the heart rate of abalone in response to low salinity stress - Grace Afumwaa Boamah; Feng Yu; Yawei Shen; Weiwei You; Changan Xu; Xuan Luo; Caihuan Ke (Aquaculture International, 2022)

Clinical and microbiological characteristics of adults with hospital-acquired pneumonia: a 10-year prospective observational study in China - Yuyao Yin; Chunjiang Zhao; Henan Li; Longyang Jin; Qi Wang; Ruobing Wang; Yawei Zhang; Jiangang Zhang; Hui Wang; Chunxia Yang; Bin Cao; Yingmei Liu; et al. (European Journal of Clinical Microbiology & Infectious Diseases, 2021)

Carbon pools and fluxes in the China Seas and adjacent oceans - Nianzhi Jiao; Yantao Liang; Yongyu Zhang; Jihua Liu; Yao Zhang; Rui Zhang; Meixun Zhao; Minhan Dai; Weidong Zhai; Kunshan Gao; Jinming Song; Dongliang Yuan; et al. (Science China Earth Sciences, 2018)

Modeling the contribution of the microbial carbon pump to carbon sequestration in the South China Sea - Wenfang Lu; Yawei Luo; Xiaohai Yan; Yuwu Jiang (Science China Earth Sciences, 2018)

LC–MS/MS-Based Metabolome Analysis of Biochemical Pathways Altered by Food Limitation in Larvae of Ivory Shell, Babylonia areolata - Jingqiang Fu; Minghui Shen; Yawei Shen; Wengang Lü; Miaoqin Huang; Xuan Luo; Jinjin Yu; Caihuan Ke; Weiwei You (Marine Biotechnology, 2018)

The differential expression of novel circular RNAs in an acute lung injury rat model caused by smoke inhalation - Zhiqiang Ye; Xuhui Liu; Yuewu Yang; Xianling Zhang; Ting Yu; Shigeng Li; Yawei Feng; Gangjian Luo (Journal of Physiology and Biochemistry, 2018)

SNP detection by parallel targeted sequencing from degraded DNA samples in Haliotis diversicolor - Peng Ren; Yawei Shen; Zekun Huang; Miaoqin Huang; Xuan Luo; Jin-Chywan Gwo; Caihuan Ke; Weiwei You (Conservation Genetics Resources, 2017)

Processes of coastal ecosystem carbon sequestration and approaches for increasing carbon sink - Yao Zhang; MeiXun Zhao; Qiu Cui; Wei Fan; JiaGuo Qi; Ying Chen; YongYu Zhang; KunShan Gao; JingFeng Fan; GuangYi Wang; ChongLing Yan; HaoLiang Lu; et al. (Science China Earth Sciences, 2017)